PERLUASAN SEKOLAH MENENGAH KEJURUAN DAN IMPLIKASINYA TERHADAP KEBUTUHAN GURU - Sunyoto, - (Lembaran Ilmu Kependidikan, 2007)
The current important governments policy (Depdiknas) is that the departmentincreases the number of vocational high school students (SMK) so that it is higherthan the number of general senior high school students (SMA). The ratio of SMK andSMA students in 2010 would be around 50:50, and in 2015 around 70: 30. Theimplication of the policy is that the t ratio of SMK and SMA teachers should ideallyalso be equal to the students of SMK and SMA. The need of SMK teachers is notmerely a quantitative matter but also qualitative one. SMK teachers should bequalified and have a competence relevant with the programs offered at the school. Tofulfill the need of SMK teachers, there should be an agreement with other institutionsespecially the institutions which produce SMK teachers.Kata kunci: perluasan, kebutuhan, guru SMK